(untitled) (LIS TODAY, 2023)
In modern library management system users take help from the Online Public Access Catalogue (OPAC) to find their required documents available in the library. This study focuses on the Authority Control process in computerized cataloguing management of library documents. Authority Control process is a key concept of OPAC where users find out their topics in easy way. The present paper structured by practical observations of the Authority Control process in Koha software. Several authority control methods were applied during this study and all have been mentioned through different figures available in this paper. The practical approaches are remembered for the piece of the procedure utilized for the assessment of this paper. Thus, the specialized abilities and different angles are methodologies of this exploration paper. If the authority control system is applied while entering the bibliographic details of the documents stored in the library, the task of searching the information by the reader also becomes simplified besides making the database of the library strong.